SCIENCE, ENGINEERING, AND TECHNOLOGY OF DYE SENSITIZED SOLAR CELLS: A DIDACTICAL DESIGN BASED ON TECHNOCHEMISTRY EDUCATION - Ahmad Mudzakir; Hernani Hernani; Galuh Yuliani; Dian Mustikasari (Jurnal Tadris Kimiya, 2020)
This research was conducted to build a view of the nature of science and technology (VNoST) chemistry education students' ability through the didactical design reconstruction. The material taken is Dye-Sensitized Solar Cells (DSSCs) topic with technochemistry education model. It is a model that looked at education from the perspective of engineers and scientists who work not only on inquiry but also on a design perspective. Based on literature research, Indonesian students had low academic literacy performance as revealed in PISA (Program for International Student Assessment) study from 2000-2015. This problem can be caused by a weak teacher's abilities of the nature of science and technology (VNoST). This research's method is Research and Development (R&D) through the Model of Educational Reconstruction (MER). The instruments used were the VNoST questionnaire, interview guidelines, and content analysis guidelines. This study's subjects were 25 prospective chemistry education students in the 6th semester for pre-conception study and ten students for implementation study at one of State Universities in Indonesia. The didactical design of learning that has been developed had several advantages, including the prediction of student responses and the anticipation of educators as well as the essential material that is a barrier to student learning. Analysis of the VNoST understanding construction patterns is explored further so that the reasons that underlie students in defining science and technology and their relationship are obtained. The implementation study proved that understanding VNoST students after attending didactical design learning improved by changing students' views on science and technology to be more accurate.